Analisis Framing Pemberitaan Tragedi Kanjuruhan Pada Media Online Detik.com dan Radar Malang (Analisis Framing Zhong Dang Pan dan Gerald M. Kosicki) - Zaena Hanifah; Hendra Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
In this study, it discusses the framing analysis of the news of the Kanjuruhan Tragedy on the Detik.com media and Radar Malang. This study aims to find out how the two media construct the reality of an event. In Detik.com media and Radar Malang, both discussed the families of the victims of the Kanjuruhan Tragedy who went to a number of agencies to ask for justice. The method used in this study is descriptive qualitative using the framing theory of Zhong Dang Pan and Gerald M. Kosicki. Based on the results of research that in the Detik.com media and Radar Malang there are similarities and differences in framing the same news. The framing analysis of the news is reviewed through syntactic, thematic, scripted and rhetorical structures.